The Oncolytic Adenovirus Δ24‐RGD in Combination With Cisplatin Exerts a Potent Anti‐Osteosarcoma Activity. (October 2014) - Martinez‐Velez, Naiara; Xipell, Enric; Jauregui, Patricia; Zalacain, Marta; Marrodan, Lucía; Zandueta, Carolina; Vera, Beatriz; Urquiza, Leire; Sierrasesúmaga, Luis; Julián, Mikel San; Toledo, Gemma; Fueyo, Juan; et al.
ABSTRACT Osteosarcoma is the most common malignant bone tumor in children and adolescents. The presence of metastases and the lack of response to conventional treatment are the major adverse prognostic factors. Therefore, there is an urgent need for new treatment strategies that overcome both of these problems. Our purpose was to elucidate whether the use of the oncolytic adenovirus Δ24‐RGD alone or in combination with standard chemotherapy would be effective, in vitro and in vivo, against osteosarcoma. Our results showed that Δ24‐RGD exerted a potent antitumor effect against osteosarcoma cell lines that was increased by the addition of cisplatin. Δ24‐RGD osteosarcoma treatment resulted in autophagy in vitro that was further enhanced when combined with cisplatin. Of importance, administration of Δ24‐RGD and/or cisplatin, in novel orthotopic and two lung metastatic models in vivo resulted in a significant reduction of tumor burden meanwhile maintaining a safe toxicity profile. Together, our data underscore the potential of Δ24‐RGD to become a realistic therapeutic option for primary and metastatic pediatric osteosarcoma. Moreover, this study warrants a future clinical trial to evaluate the safety and efficacy of Δ24‐RGD for this devastating disease. © 2014 American Society for Bone and Mineral Research.